Some Models of Linguistic Understanding - Guy Longworth (Baltic International Yearbook of Cognition, Logic and Communication, 2009)
I discuss the conjecture that understanding what is said in an utterance is to be modelled as knowing what is said in that utterance. My main aim is to present a number of alternative models, as a prophylactic against premature acceptance of the conjecture as the only game in town. I also offer preliminary assessments of each of the models, including the propositional knowledge model, in part by considering their respective capacities to sub-serve the transmission of knowledge through testimony. In each case, the preliminary assessment is unfavourable. I end by very briefly sketching an additional model as an object for future consideration.